MANUFACTURE OF CHEMFUN GAME BOARD LEARNING MEDIA IN SCIENCE LITERATION ORIENTED CHEMICAL BONDING MATERIALS - Teti Fathonah; Cucu Zenab Subarkah; Sari Sari (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to analyze the results of the validation and describe the appearance of the board game learning media on chemical bonding material based on scientific literacy. This game board is expected to be a tool in learning about chemical bonding material which is then oriented to scientific literacy. Chemical bonding is an important concept that is to understand other topics in chemistry. This research method uses Design Based Research. The results of the validation of this game obtain data that this game is suitable for use as a learning medium with the validation test results of 0.86. So this shows that the learning media for the Chemfun board game of chemical bonds oriented to scientific literacy is valid to be developed in learning. The display of learning media for chemical bond chemfun board games, including questions and materials, which is equipped with pictures of chemical bonds oriented to scientific literacy, which contain aspects of context, content, process, and attitudes.